Sedimentary Characteristics of the Neogene in the Eastern Liaodong Area, Bohai Sea, China - Ranran Hao; Yongshi Wang; Jing Wang; Zhiping Wu; Anyu Jing; Xiaolin Liu; Haoqing Xu; Qunhu Wu (Energies, 2022)
The sedimentary characteristics of the Neogene in the eastern Liaodong area are poorly studied, which restricts the oil and gas exploration in this area. Based on the current seismic, logging, drilling, and core data, we have studied the sequence stratigraphy and sedimentary characteristics of the Neogene in the eastern Liaodong area. Ultimately, we identified the controlling factors of sedimentation and established the depositional model. In this study, six sequence boundaries of the Neogene were identified and can be divided into five third-order sequences. The sedimentary evolution can be divided into four stages: braided river delta, meandering river delta with a low sand-stratum ratio, meandering river delta with a high sand-stratum ratio, and meandering river delta. Both the palaeotectonic movements and paleoclimate changes of the Neogene influence the periodical fluctuation of the lake level and then control the vertical evolution of the sedimentary types. The paleogeomorphology controls the macroscopic distribution of the sedimentary facies zone, the paleo-valleys that are associated with the strike-slip faults control the channel strike, and the fault slopes at the edge of the lacustrine basins control the sand redistribution of the delta front.